Effects of an information shock on registry-based health indicators: Evidence from a Swedish PFAS crisis - Mikael Elinder; Oscar Erixson; Erik Grönqvist; Sophie Langenskiöld; Mattias Öhman (PLoS ONE, 2026)
This study investigates how the public announcement of very high levels of the toxic chemicals PFAS in the drinking water in Kallinge, Sweden, impacted the health of local residents. By leveraging the unexpected timing of the announcement and utilizing high-frequency individual-level healthcare data, we can isolate the effects of the information shock independently of any toxic effects of PFAS exposure. Despite numerous reports of distress and concern among those affected, our analysis reveals no significant increase in health care utilization following the announcement, as measured by prescription drug use and specialist healthcare visits. This finding holds true even when specifically examining mental health-related care, prescriptions of antidepressants, and sleeping medications. Overall, our results suggest that both the affected community and public authorities managed the situation effectively, mitigating potential health consequences related to anxiety.